Technical-Economic-Environmental Analysis for the Implementation of Hybrid Energy Systems - Oliveros-Cano, Luis; Salgado-Meza, Juan; Robles-AlgarÃn, Carlos (International Journal of Energy Economics and Policy, 2019)
In this paper, a technical-economic-environmental analysis was carried out to establish the feasibility of implementing different types of hybrid energy systems. Four hybrid systems (solar-wind) were designed: with battery, with gas generator, grid-connected and with a diesel generator. These systems were analyzed using the HOMER software, which allows the calculation of pollutant gas emissions and simulates and optimizes energy consumption based on energy demand and energy resources. For the financial analysis, the net present value (NPV), the internal rate of return (IRR) and the payback period (PBP) were used, which were calculated using Microsoft Excel. The four systems were designed for the energy demand of the luminaires of the academic building of the Universidad del Magdalena. The results obtained show that the first three systems are profitable for their implementation taking into account the capacity of power generation, gas emissions and the PBP. Keywords: Hybrid Energy System, Environmental Analysis, Financial Analysis JEL Classifications: Q42, Q51, G00 DOI: https://doi.org/10.32479/ijeep.8473